السعي الروسي عبر التحالفات الدولية والأزمات الراهنة لإقامة نظام دولي متعدّد الأقطاب - حسون محمد; ناصوري أحمد; محمد فادي محمد مالك (Latakia University Journal - Economic and Legal Sciences Series, 2016)
يتناول البحث مساعي روسيا الاتحادية لكسر التفرّد الأميركي بقيادة العالم، كما يبحث قدراتها وإمكانية بقاءها قوةً عالميةً تؤخذ بعين الاعتبار، لاسيما في ظلّ الحروب التي اشتعلت في المنطقة العربية الشرق الأوسط (حروب الخليج العربي، وخاصة احتلال العراق عام 2003) تلك الحروب التي قسمت المجتمع الدولي، وفسحت المجال لروسيا بالانطلاق لإنشاء بعض التحالفات الدولية، كمحاولةٍ للوقوفِ بوجهِ التفرّد الأميركي بقيادة العالم، وتشكّل الأزمة السورية نموذجاً مهمّاً في تلك السياسة، إضافةً لقيام روسيا مجدّداً بالتلويح بالورقة النووية، وتذكير العالم بأنها لازالت قوّة كبرى لها مكانتها وحضورها المؤثّر على الساحة الدولية. كما يتناول البحث الدور الأوروبي في مواجهة الولايات المتحدة الأميركية، مما دفع بروسيا للبحث عن حلفاء خارج أوروبا في إطار محاولاتها لخلق عالمٍ متعدّد الأقطاب. The research efforts of the Russian Federation to break the exclusivity U.S. led the world, and looking capabilities and the possibility of survival is a global power are taken into consideration, especially in light of the wars that broke out in the Middle East (the wars of the Arabian Gulf, and especially the occupation of Iraq in 2003) those wars that divided the international community, and I let area for Russia to go ahead for the establishment of some international alliances, work stand against exclusivity U.S. led the world, and constitute the Syrian crisis an important model in that policy, as well as LG do Russia again waved the nuclear card, and to remind the world that it is still a major force her strong presence influential in the international arena. It also addresses the role of European research in the face of the United States, prompting Russia to search For allies outside Europe in its attempts to create a multipolar world.